Utilization of Automatic Packet Reporting System (APRS) for Weather Station Monitoring - Sonny Dwi Harsono; Nur Salma Y.H; Zhauhar *; Rifki Ardinal (Spektral, 2022)
Nowadays, weather monitoring is indispensable. The data obtained in the present or past can be a reference to predict future weather, can be used to determine the condition of the antenna on ground stations in the face of extreme weather. It is necessary to have a tool that can read the parameters of the weather, because the importance of weather monitoring. Automatic Weather Station (AWS) This type of ADS-WS1 is a tool that can read several parameters of weather quantities such as rainfall, wind direction, wind speed, temperature, humidity, and pressure. It has equipped with sensors to read the number of weather parameters. ADS-WS1 not using internet networks, but use radio frequencies for sending a sensor data that has connect to the transceiver. With that frequency the signal will be transmitted and received via satellite or terrestrials with Automatic Packet Reporting System (APRS) through radio frequency and Internet gateway or known as (iGate). The result from the sensor that have been installed at the PUSTEKSAT ground station can be monitored both on Radio Frequency (RF) and Internet, the purpose of this research is to send weather data station with APRS format via Radio frequency,  this  a proof of concept for sending weather information via APRS format system. Keywords- AWS, APRS, Radio, ADS-WS1, Frequency